(untitled) (Simbiótica. Revista Eletrônica, 2020)
This article aims to discuss the problem of the Covid-19, a viral disease that has become the main political problem nowadays and which is likely to have devastating effects for several decades to come. Specifically, the relationship between coronavirus and globalization is questioned. It is argued that Covid-19 is not a super disease and its pandemic character was achieved only due to the expansion of new technologies that allow shortening distances and accelerating contacts between peoples. It is suggested that in order to avoid further crises in the future, it will be necessary to modify the world political imagination. It will be necessary to accept the idea that we all live on the same planet and that we must become a global political community. Keywords: Covid-19; coronavirus; globalization; international politics.